Spatial Distribution of Biochemical Parameters Indicating Biomass and Community Composition of Microbial Assemblies In Estuarine Mud Flat Sediments - Federle, Thomas W. (1983)
The spatial distribution of communities was examined in estuarine mud flat sediments by the biochemical analysis of the lipids and lipid components extracted from the sediments. Total phospholipid was used as a measure of total biomass, and fatty acids were used as indicators of community composition. Comparisons were made among 2- by 2-m (location) and 0.2- by 0.2-m (cluster) sampling plots by using a nested analysis of variance to design an optimal sampling strategy to define the microbial content of a large, relatively homogenous area. At two of the three stations, a 2- by 2-m plot was representative of the station, but 0.2- by 0.2-m areas were in no case representative of the station. The biomass measured by the extractable phospholipid and the total lipid palmitic acid showed excellent correlation with the fatty acid “signatures” characteristic of bacteria, but showed a lower correlation with the long-chain polyenoic fatty acids characteristic of the microfauna.